Kinetics of thermal decomposition of howlite mineral at different heating rates - Sen, Gamze Arslan; Yilmaz, Muege Sari; Derun, Emek Moroydor (YILDIZ TECHNICAL UNIV, 2023)
In this work, the thermal decomposition kinetics of howlite were investigated at different heating rates by using Coats-Redfern, Ozawa, and Kissinger-Akahira-Sunose kinetic models under non-isothermal conditions. The thermal decomposition of howlite occurred in two dehydroxylation stages. Results indicated that it decomposes in the first dehydroxylation stage at a very slow rate due to the higher thermal stability of the mineral. Kinetic parameters were determined using the above-mentioned models for all decomposition stages. The activation energies calculated from the Ozawa and Kissinger-Akahira-Sunose isoconversional methods fit well with each other, while the activation energies calculated with the Coats-Redfern method were different. It was also seen that the activation energy of the decomposition reaction changed with the degree of conversion, suggesting that the reaction mechanism is not single-step.
Keywords: Howlite; Kinetics; Thermal Decomposition; Dehydroxylation; Isoconversional; DEHYDRATION KINETICS; ULEXITE; Engineering